Kimmeridgian–Berriasian stratigraphy and sedimentary evolution of the central Iberian Rift System (NE Spain). (November 2019) - Aurell, M.; Bádenas, B.; Canudo, J.I.; Castanera, D.; García-Penas, A.; Gasca, J.M.; Martín-Closas, C.; Moliner, L.; Moreno-Azanza, M.; Rosales, I.; Santas, L.; Sequero, C.; et al.
Abstract: Sequence-stratigraphic, biostratigraphic and strontium-isotopic data have made it possible to update what is known of the stratigraphy and sedimentary evolution of the Kimmeridgian–Berriasian synrift successions recorded in four subbasins (Aguilón, Oliete, Morella, Galve) of the central Iberian Rift System (NE Spain). The studied successions are arranged in three unconformity-bounded synrift sequences. Synrift sequence 1A (Kimmeridgian–mid-early Tithonian) includes four transgressive-regressive sequences deposited on low-angle carbonate ramps, characterized by shallow-water grain-supported facies and coeval open-marine rhythmic successions of marls and lime mudstones (overall thickness ranging from 120 to 250 m). Ammonite biostratigraphy, combined with the last occurrence of Alveosepta jaccardi (Schrodt) and strontium-isotopic data constrains the Kimmeridgian-Tithonian boundary towards the uppermost part of synrift sequence 1A. Synrift sequence 1B (mid-early Tithonian to mid-Berriasian) consists of coastal to shallow-marine carbonate to mixed carbonate-siliciclastic successions, with a continuous record in the depocentral areas of the Morella and Galve subbasins (up to 365 m in thickness). Anchispirocyclina lusitanica (Egger) is common in the lower and middle part of the sequence, whereas charophytes of the lower Berriasian Globator maillardii maillardii Zone are recorded in its upper part. Strontium-isotopic data and ostracods whose first occurrence is Berriasian, indicate that the Tithonian-Berriasian boundary is located towards the mid-upper part of the synrift sequence 1B. Synrift sequence 1C (mid-Berriasian–mid-early Valanginian) is locally recorded in the Galve subbasin and consists of siliciclastic continental successions (up to 100 m in thickness). The available biostratigraphic data (charophytes, ostracods, sporomorphs) indicate that this sequence was deposited upwards from early Berriasian Globator maillardii incrassatus Zone. The presence of the lower Valanginian successions at the upper part of synrift sequence 1C in certain subsiding areas of the Galve subbasin cannot be ruled out. The sequence-stratigraphic and biostratigraphic data reported here indicate that the Galve and Morella subbasins started to develop during the Kimmeridgian. Successive stages of tectonic activity affected these subbasins during the mid-early Tithonian, the mid-Berriasian, and around the Berriasian-Valanginian transition. The stratigraphy and tectono-sedimentary evolution of the central Iberian Rift System indicate that the Berriasian successions are linked to the "Jurassic cycle".